2016
DOI: 10.1155/2016/4794576
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomic Functions of PPARs in Obesogenic Environments

Abstract: Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that mediate the effects of several nutrients or drugs through transcriptional regulation of their target genes in obesogenic environments. This review consists of three parts. First, we summarize current knowledge regarding the role of PPARs in governing the development of white and brown/beige adipocytes from uncommitted progenitor cells. Next, we discuss the interactions of dietary bioactive molecules, such as fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 200 publications
0
11
0
1
Order By: Relevance
“…Unsaturated fatty acids are further ligands of the PPARs and activation of these nuclear receptors contributes to the metabolic and anti-inflammatory activities of these lipids [81]. RvE1 suppressed activation of NF-κB by a mechanism which partly depends on PPAR [82].…”
Section: Molecules Involved In Resolution Of Inflammationmentioning
confidence: 99%
“…Unsaturated fatty acids are further ligands of the PPARs and activation of these nuclear receptors contributes to the metabolic and anti-inflammatory activities of these lipids [81]. RvE1 suppressed activation of NF-κB by a mechanism which partly depends on PPAR [82].…”
Section: Molecules Involved In Resolution Of Inflammationmentioning
confidence: 99%
“…Previous studies have confirmed that peroxisome proliferator-activated receptors (PPARs) play a crucial role in regulating fatty acid oxidation and the upstream rate-limiting enzyme of fatty acid oxidation, carnitine palmitoyltransferase 1. 8 Despite similar structures, the three PPAR isotypes α, β, and γ vary greatly in their tissue distribution, pharmacology, type of endogenous ligand, and biological effects. Especially in the liver, PPARα acts as a master regulator of liver metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of PPARγ is either ligand-dependent due to the conformational change of the LBD or ligand-independent due to the kinase-mediated phosphorylation of the A/B domain [10]. Primed PPARγ can regulate target gene expression both positively and negatively by binding to specific PPREs in the regulatory sites of these genes [29]. The large Y-shaped ligand binding domain allows PPARγ to recognize many different ligands and to flexibly interact with ligands, which makes it possible for PPARγ to respond to various environmental stimuli and to modulate the expression of target genes [30].…”
Section: Structure Ligands and Signaling Pathways Of Pparγmentioning
confidence: 99%